Effect of kieselguhr on filtration of first carbonatation sludge - Togrul, H; Arslan, N (Int Sugar Journal Ltd, 1995)
A study was made on the filtration of first carbonatation sludge at different temperatures and pressures. The measurement of the average specific cake resistance is discussed. The effects were investigated of varying the precoating amount and the filter aid dose on the specific cake resistance of mud from constant pressure filtration. It was found that the cake obtained from filtering first carbonatation sludge was compressible.